PROTRUSION OF GENITALIA THROUGH VAGINAL TEAR IN A BUFFALO - CHAUHAN, P M; NAKHASHl, H C; RAJAN, B M; BHAVSAR, J A; SHARMA, V K (The Indian Journal of Animal Reproduction, 2015)
The present communication deals with the management of an unusual protrusion of post-partum involuting internal genitalia through a left dorso-lateral vaginal tear in a recently calved Mehsana buffalo.